Provincialising Futures Literacy: A caution against codification. (October 2021) - Facer, Keri; Sriprakash, Arathi
Highlights: Recent years have witnessed the emergence of an international effort to codify a new 'human capability': Futures Literacy. We draw on education and literacy studies to identify risks in promoting a universal and codified form of Futures Literacy. We argue that there are better ways of cultivating collective human capacities for using the future in education. These recognise already existing futures literacies and provincialise 'Futures Literacy' as a situated phenomenon. And build alliances between advocates of futures literacy and critical education traditions. Abstract: This paper reflects on the emergence of an international effort to codify and cultivate a new 'human capability': Futures Literacy. Futures Literacy is understood as the technical expertise to reflexively 'use the future' to perceive and inform actions in the present. Its advocates call for Futures Literacy to become a new 'universal literacy'. While the critical use of ideas of the future to inform action in the present is an educational practice with generative pedagogic and political possibilities, in this paper we show that codifying Futures Literacy in this way risks narrowing what constitutes 'rational' uses of the future, positioning a small technocratic elite as authorities in its practice and casting other uses of the future as forms of illiteracy. The paper proposes a different trajectory for 'Futures Literacy', in which it divests from assumptions of institutional authority and desires for universal codification, positions itself as one amongst many futures literacies and as allied with a broader repertoire of educational and social struggles over the future. In provincialising Futures Literacy in this way it will be better placed to creatively surface and grapple with the relations of power through which ideas of the future are brought into the present.